Pengaruh Kompensasi Non Finansial Dan Reduction Job Stres Terhadap Kinerja Karyawan - Devi Kurnia Mandansari; Honorata Ratnawati Dwi Putranti (Universitas Veteran Bangun Nusantara, 2024)
This research aims to empirically test the effect of non-financial compensation and job stress reduction on employee performance. Non-financial compensation and reducing job stress have an important role in improving employee performance. This type of research uses quantitative research by distributing questionnaires to respondents. The population of this research is employees at manufacturing company